Field-based simulation of a demonstration site for carbon dioxide sequestration in low-permeability saline aquifers in the Ordos Basin, China - Xie, J.; Zhang, K.; Hu, L.; Pavelic, Paul; Wang, Y.; Chen, M. (Springer, 2015)
Saline formations are considered to be candidates for carbon sequestration due to their great depths, large storage volumes, and widespread occurrence. However, injecting carbon dioxide into low-permeability reservoirs is challenging. An active demonstration project for carbon dioxide sequestration in the Ordos Basin, China, began in 2010. The site is characterized by a deep, multi-layered saline reservoir with permeability mostly below 1.0×10-14 m2. Field observations so far suggest that only small-to-moderate pressure buildup has taken place due to injection. The Triassic Liujiagou sandstone at the top of the reservoir has surprisingly high injectivity and accepts approximately 80 % of the injected mass at the site. Based on these key observations, a three-dimensional numerical model was developed and applied, to predict the plume dynamics and pressure propagation, and in the assessment of storage safety. The model is assembled with the most recent data and the simulations are calibrated to the latest available observations. The model explains most of the observed phenomena at the site. With the current operation scheme, the CO2 plume at the uppermost reservoir would reach a lateral distance of 658 m by the end of the project in 2015, and approximately 1,000 m after 100 years since injection. The resulting pressure buildup in the reservoir was below 5 MPa, far below the threshold to cause fracturing of the sealing cap (around 33 MPa).